Modifikasi Alat Pemetik Buah Pala Model Galah DTR TETA 19 - rossok, demianus; Ludong, Daniel; Lengkey, Lady (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2024)
This study aims to modify the nutmeg harvesting tool pole model prototype 1 and test the performance of nutmeg harvesting tool pole model that has been modified or harvesting tool DTR TETA 19. This study uses experimental methods, tools that have been modified and then tested to determine the performance of the tool by calculating the harvesting capacity of the fruit/minute and also the capacity of the fruit/hour. The data obtained are arranged in Tabular Form and analyzed descriptively. The conclusion of this study is DTR Teta 19 harvesting tool is superior to the previous tool or nutmeg harvesting tool pole model prototype 1, where DTR Teta 19 tool has an average capacity with two harvests of 199 pieces/hour, while the harvesting capacity of the prototype 1 harvesting tool with one harvest of 152 pieces / hour has a difference of 47 pieces (harvesting with a tool length of 200 cm). As for harvesting with a tool length of 300 cm has a difference in harvesting capacity of 56 pieces / hour where the tool DTR TETA 19 superior. and harvesting with a tool length of 400 cm harvesting tool DTR TETA 19 is superior to the difference in harvesting capacity of fruit / hour which is 21 pieces.